2000
DOI: 10.1136/jnnp.68.6.774
|View full text |Cite
|
Sign up to set email alerts
|

Fatal familial insomnia: clinical, neuropathological, and genetic description of a Spanish family

Abstract: The clinical presentation and evolution, neuropathological findings, and genotyping of three members of a Spanish family aVected with fatal familial insomnia are reported. The mother and two of her oVspring developed a rapidly evolving disease with insomnia and behavioural disorders as the initial symptoms and died between 5 and 10 months after the onset of the illness. Frontal brain biopsy in the mother disclosed only non-significant spongiosis, and full neuropathological examination of her oVspring showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…In other types of human genetic prion disease, for example FFI, massive gliosis in the thalamus is regular but PrP Sc deposition is usually mild. 17 The inconsistency of PrP Sc deposits and gliosis in some brain regions of CJD may reflect that gliosis in prion diseases is a common mechanism for reacting to neuron degeneration. Actually, various degrees of gliosis have been observed in other neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In other types of human genetic prion disease, for example FFI, massive gliosis in the thalamus is regular but PrP Sc deposition is usually mild. 17 The inconsistency of PrP Sc deposits and gliosis in some brain regions of CJD may reflect that gliosis in prion diseases is a common mechanism for reacting to neuron degeneration. Actually, various degrees of gliosis have been observed in other neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic investigations revealed a D178N mutation of the prion protein with a Val/Met polymorphism on position 129 and Met on the mutated allele, thus making the diagnosis of FFI, and more specifically indicating the slowly progressive subtype of FFI. 5 Postmortem macroscopic examination of the brain solely showed ventricular enlargement and minor cerebellar atrophy. Histologic study revealed severe neuronal loss and astrogliosis in the thalamus (particularly mediodorsal, centromedian, and reticular nuclei), with spongiform change mainly in ventrolateral nuclei, as well as marked gliosis in the inferior olivary nucleus (without spongiform change) and the dentate nucleus of the cerebellum (Figure 2B-C).…”
Section: Observationmentioning
confidence: 98%
“…61 is associated with ataxia and dysarthria at onset, and after prolonged disease, with widespread neuropathological damage and cortical spongiosis. 62,63 Biochemically, FFI is quite distinct from other prion diseases: the prions involved in fCJD and sCJD give a B21 kDa protein fragment after digestion with protease, while FFI produces i a shorter, B19 kDa, protein fragment. 64 These results further confirm the ''prion strain'' hypothesis, allowing researchers to identify two different strains from their origin to their experimental transmission to laboratory animals.…”
Section: Kurumentioning
confidence: 99%